2007
DOI: 10.2337/dc07-0114
|View full text |Cite
|
Sign up to set email alerts
|

Objectively Measured Light-Intensity Physical Activity Is Independently Associated With 2-h Plasma Glucose

Abstract: OBJECTIVE -We examined the associations of objectively measured sedentary time, lightintensity physical activity, and moderate-to vigorous-intensity activity with fasting and 2-h postchallenge plasma glucose in Australian adults.RESEARCH DESIGN AND METHODS -A total of 67 men and 106 women (mean age Ϯ SD 53.3 Ϯ 11.9 years) without diagnosed diabetes were recruited from the 2004 -2005 Australian Diabetes, Obesity, and Lifestyle (AusDiab) study. Physical activity was measured by Actigraph accelerometers worn du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
452
4
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 534 publications
(489 citation statements)
references
References 26 publications
28
452
4
5
Order By: Relevance
“…Several recent studies indicated that objective measured light-intensity PA is beneficially associated with blood glucose and other metabolic risk factors. 18,[25][26][27] Taken together, these findings suggested that the favorable effect of light PA on arterial stiffness is mediated by metabolic profile improvement. Other mechanisms by which daily light PA may influence arterial stiffness in older people are still speculative and include the effects of PA on the bioavailability of NO, vascular smooth muscle tone, connective tissue cross-linking, and gene expression.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Several recent studies indicated that objective measured light-intensity PA is beneficially associated with blood glucose and other metabolic risk factors. 18,[25][26][27] Taken together, these findings suggested that the favorable effect of light PA on arterial stiffness is mediated by metabolic profile improvement. Other mechanisms by which daily light PA may influence arterial stiffness in older people are still speculative and include the effects of PA on the bioavailability of NO, vascular smooth muscle tone, connective tissue cross-linking, and gene expression.…”
Section: Discussionmentioning
confidence: 68%
“…15,16 Objective evidence has been reported indicating that light PA has a relatively high energy cost during daily living 13,17 and is beneficially associated with traditional risk factors. 18 Therefore, we hypothesized that the longer time spent in light PA assessed by triaxial accelerometry may be associated with reduced arterial stiffening. Moreover, it is also unclear whether the effects of light PA are the same in fit and unfit individuals.…”
mentioning
confidence: 99%
“…Few other studies have looked at insulin levels to help clarify these observations. An association between sedentary time and 2 h plasma glucose has been reported [28], but in contrast to results from healthy adults, no association was found between sedentary time and insulin resistance in adults with a family history of diabetes [22].…”
Section: Discussionmentioning
confidence: 85%
“…16,17 Because exergames can be played in a variety of settings including unsafe neighborhoods, 18 they can increase opportunities for youth to engage in PA 11,12,16,19,20 and decrease sedentary behavior. 18,19,[21][22][23][24][25] Exergaming may have added value in youth compared with adults because young people are generally more physically active (ie, move more) while exergaming, 26 and game exertion (effort) is not a deterrent to exergaming. 27 Exergaming may be more enjoyable than sedentary video games and treadmill workouts, 28 and they provide youth with opportunities to try a range of sports (eg, boxing, kung fu), which may in turn increase motivation to become involved in these activities at school or local sports centers.…”
mentioning
confidence: 99%